Pemberdayaan Kader Posyandu Dalam Mencegah Penyakit Gigi dan Mulut Balita Di Desa Kukuh Kecamatan Marga Kabupaten Tabanan Tahun 2018 - I Nyoman Wirata; Ni Ketut Ratmini; Ni Wayan Arini; Ni Made Sirat (Jurnal Pengabmas Masyarakat Sehat, 2019)
Problems that are considered urgent in dental health programs in Indonesia today are still high rates of dental caries and periodontal disease. The optimal dental health status of the community can be achieved by increasing promotive and preventive efforts from an early age to the elderly. Community target who became the purpose of the implementation of community service is a cadre of Posyandu in Kukuh Village District Marga Tabanan regency. The purpose of Community Service is to empower Posyandu cadres in preventing tooth and mouth disease in Toddlers, thus increasing the degree of oral health of the people in Kukuh Village Penebel District Tabanan Regency Year 2018. Implementation of activities in community service is done by demonstrating how to brush teeth in front of the posyandu cadres. The activity targets are all posyandu cadres in Kukuh village, amounting to 40 people, then applying cadre to posyandu visitors in every posyandu at every posyandu activity. The result of community service is the cadres can demonstrate how to brush their teeth properly and have been practiced in the field in posyandu activities to be given to Posyandu visitors.Keywords: Empowerment of Posyandu cadres, Brushing Teeth.